Exploring the Role of Children’s Literature in Developing Literacy and Character in Elementary Education: A Qualitative Study - Rizal Ibrahim Aji; Unes Unes; Syamsurrijal Syamsurrijal (Journal of General Education and Humanities, 2025)
This study was motivated by the limited empirical research on the role of children's literature as an integrative medium in improving literacy and character education in Indonesian elementary schools. This study aims to analyze the contribution of children's literature to the improvement of literacy skills and character development among students at SD NU Kaplongan. The method used is a descriptive, qualitative survey approach to gain an in-depth understanding of literacy practices in children's literature. Data were collected through questionnaires, semi-structured interviews, and document analysis, involving 29 fifth-grade students, a classroom teacher, and the school principal. The analysis technique used was thematic content analysis to identify major patterns in reading habits, pedagogical strategies, and institutional support. The study found that about 82% of students experienced increases in reading fluency, story comprehension, and moral reflection after implementing children's literature-based literacy. Teachers used picture books and themes relevant to students' interests, while the school provided support through the SAMIKU (One Week, One Book) program and library facilities. However, the students' reading culture was still incidental and had not become a sustainable habit. Scientifically, this study reinforces the effectiveness of literature-based pedagogy in holistic literacy learning, while practically providing an implementable model for schools to integrate literacy and character. Further research is recommended to explore the digital adaptation of children's literature in fostering motivation and media literacy in the era of 21st-century learning.